Carimontir: Motor vehicle service application - Muhammad Akbar Indraputra; Edi Hamdi (Institute of Computer Science (IOCS), 2023)
The number of motorized vehicles in Indonesia is increasing, people's mobility is also increasing so that it often creates problems regarding the motorized vehicles used to carry out activities. The problem that often occurs is in the aspect of service. This has prompted the emergence of the carimontir application which helps with various motor vehicle maintenance problems. Unfortunately, studies on the carimontir application have not been carried out in depth so that researchers are interested in studying Carimontir: motorized vehicle service applications. The research method used is qualitative with a literature study so that various data are collected for analysis and it is known from the research results that the development of the carimontir application is carried out carefully and carefully, namely analyzing external and internal factors, implementing strategies, marketing plans, operational plans, planning human capital, financial plans and risk plans to find out various things that might occur so that they can be minimized and prevented quickly and precisely.